Good and Bad English: How to Deal with Language Variation and Change in Language Learning - Ikmi Nur Oktavianti (Universitas Ahmad Dahlan, 2015)
AbstractLanguage practitioners often seem language phenomena as degeneration or decay. This is something misleading and need to be taken seriously into consideration. Purists and prescriptivists should see the phenomena not only from the normative point of view but also from the science of language itself, which is still forgotten. This article thus attempts to propose insights from linguistics related to the term good and bad language, with the focus on good and bad English. Is there any good and bad language? The answer to the question can only be given at best by elaborating the linguistics concept. This discussion is of benefit for language learning of which it is closely related.